2023
DOI: 10.1002/smll.202301625
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive and Intrinsically Fuel Sensing Metal–Organic Framework Motors for Tailoring Collective Behaviors of Active‐Passive Colloids

Abstract: Microorganisms display nonequilibrium predator–prey behaviors, such as chasing–escaping and schooling via chemotactic interactions. Even though artificial systems have revealed such biomimetic behaviors, switching between them by control over chemotactic interactions is rare. Here, a spindle‐like iron‐based metal–organic framework (MOF) colloidal motor which self‐propels in glucose and H2O2, triggered by UV light is reported. These motors display intrinsic UV light‐triggered fuel‐dependent chemotactic interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The motion of the BMT-micromotors in the presence of different molar solutions of NaCl is shown in Figure S6. It can be observed that the speed of the micromotor slows down with the concentration of the NaCl solution in the presence of 1.0 wt % H 2 O 2 , which is consistent with the ionic self-diffusiophoresis mechanism of the reported work. , As shown in the first image of Figure c and Video S1e, in the absence of UV light, the micromotor exhibits Brownian motion even in 0.5 wt % H 2 O 2 for the first two seconds, while it shows active self-propulsion with the speed of ≈28 μm/s when the light is turned on. We observed that micromotors are highly active toward H 2 O 2 fuel, and it can actively give response even when the fuel concentration decreases to only 0.01 wt %.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The motion of the BMT-micromotors in the presence of different molar solutions of NaCl is shown in Figure S6. It can be observed that the speed of the micromotor slows down with the concentration of the NaCl solution in the presence of 1.0 wt % H 2 O 2 , which is consistent with the ionic self-diffusiophoresis mechanism of the reported work. , As shown in the first image of Figure c and Video S1e, in the absence of UV light, the micromotor exhibits Brownian motion even in 0.5 wt % H 2 O 2 for the first two seconds, while it shows active self-propulsion with the speed of ≈28 μm/s when the light is turned on. We observed that micromotors are highly active toward H 2 O 2 fuel, and it can actively give response even when the fuel concentration decreases to only 0.01 wt %.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the Si−O−M (M = Co/Zn) linkage could generate, and TPM nucleates and grows on the surface of the particles. 40,41 Finally, the nucleated TPM was thermally polymerized with the aid of an AIBN initiator. The Janus morphology of the as-prepared materials contained a smooth passive TPM part and an active rough part of the Co/Zn-NC particle (Figures 1d and S1c,d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important class of synthetic active materials are mixtures of active self-propelled colloids and passive ones [ 15 ]. Chemically propelled active colloids may attract one or multiple passive colloids via electrostatic [ 16 ], hydrophobic [ 17 ], and phoretic [ 18 21 ] interactions, self-assembling into translating clusters that hold applications in cargo loading and transportation, or exhibiting predator–prey type biomimetic functions [ 22 , 23 ]. Active colloids have also been observed to orbit around passive spheres [ 24 ] or fixed posts [ 25 ].…”
Section: Introductionmentioning
confidence: 99%